(untitled) (Progressive Agriculture, 2015)
The field experiment was conducted to investigate the alleviation of the adverse effects of soil salinity in rice by efficient management of potassium fertilizers in coastal saline areas.The salt-sensitive (BRRI dhan28) and salt-tolerant (Binadhan-10) rice cultivars were used as test crops. The experiment was laid out in a randomized complete block design with three replications. There were thirteen treatment combinations viz. T0 (no K from MoP or SoP), T1 (K100 from MoP at final land preparation), T2 (K150 from MoP at final land preparation), T3 (K200 from MoP at final land preparation), T4 (K100 from MoP in two splits), T5 (K150 from MoP in two splits), T6 (K200 from MoP in two splits), T7 (K100 from SoP at final land preparation), T8 (K150 from SoP at final land preparation), T9 (K200 from SoP at final land preparation), T10 (K100 from SoP in two splits), T11 (K150 from SoP in two splits) and T12 (K200 from SoP in two splits). Muriate of potash (MoP) and sulphate of potash (SoP) were applied in two splits and during land preparation as per treatments. Binadhan-10 (salt-tolerant) rice producedhigher grain and straw yields than salt-sensitive (BRRI dhan28) one under saline conditions. Furthermore, application of potassium fertilizers resulted in significant increases growth, and grain and straw yields of both salt-sensitive and salt-tolerant rice cultivars under saline conditions. The nutrient (NPS) uptake and K+/Na+ ratio increased in both rice cultivars by application of potassium fertilizers under saline conditions. The higher amount of yield as well as nutrient uptake of both rice cultivars was observed when SoP was applied either in land preparation or two split doses. The K+/Na+ ratio was found to be higher in T9 and T12 treatments in salt-sensitive cultivar whereas T2 and T3 treatments showed higher K+/Na+ ratio in grain and straw of salt-tolerant rice cultivar, respectively. Therefore, the present study suggests that rice productioncould be improved in saline areas through application of higher doses of potassium fertilizers particularly split application of sulphate of potash. Progressive Agriculture 26 (2): 115-121, 2015